Hirschman, Montesquieu et les philosophes écossais - Alexandra Hyard (Astérion)
The purpose of this article is to reconsider Albert O. Hirschman’s classification of the philosophers of the Scottish Enlightenment in response to Montesquieu’s “doux commerce” mechanism. Why did he rank James Steuart and John Millar among the “optimistic” supporters of the political benefits of trade? And why did he rank Adam Smith and Adam Ferguson among the “pessimistic” supporters?